2019
DOI: 10.1038/s41598-019-51332-4
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Focused Ultrasound (LOFU)-mediated Acoustic Immune Priming and Ablative Radiation Therapy for in situ Tumor Vaccines

Abstract: Focal ablative therapies have been primarily used for local tumor ablation. However, they often fail to impact systemic disease. Here we propose the use of low intensity focused ultrasound (LOFU), a noninvasive, nontoxic, conformal therapy, to deliver acoustic stress to the tumor for immune priming. We demonstrate that LOFU significantly induces expression and cell surface localization of heat shock proteins in murine breast (4T1) and prostate adenocarcinoma (TPSA23) cancer cell lines. In vivo LOFU followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Shorter treatment times of 2 min can also induce necrosis and antitumor immune responses mediated by CD8 + cells when 3-4 W/cm 2 ultrasound is combined with microbubbles (115). Finally, another recent study used shorter ultrasound treatment times of 1.5 s per spot to heat prostate tumors to 45˚C prior to radiotherapy to develop a T cell driven-in situ tumor vaccine (121). Although some preclinical and clinical studies can be found studying the antitumor effect of ultrasound-induced hyperthermia, more studies are needed to determine treatment parameters that will produce a specific immune response and whether these effects are superior to thermal ablation in certain cases.…”
Section: Thermal Ablationmentioning
confidence: 99%
“…Shorter treatment times of 2 min can also induce necrosis and antitumor immune responses mediated by CD8 + cells when 3-4 W/cm 2 ultrasound is combined with microbubbles (115). Finally, another recent study used shorter ultrasound treatment times of 1.5 s per spot to heat prostate tumors to 45˚C prior to radiotherapy to develop a T cell driven-in situ tumor vaccine (121). Although some preclinical and clinical studies can be found studying the antitumor effect of ultrasound-induced hyperthermia, more studies are needed to determine treatment parameters that will produce a specific immune response and whether these effects are superior to thermal ablation in certain cases.…”
Section: Thermal Ablationmentioning
confidence: 99%
“…Focused ultrasounds (FUs) can be also used as inductor for externally control of gene expression, penetrating with a depth of centimeters into tissues. Therapeutic FUs-controlled by Magnetic Resonance Imaging (MRI) have been applied into clinics for vasodilation, neuromodulation, heat-ablation of tumors and as an adjuvant therapy for drug, gene delivery (124) and tumor vaccination in situ (125). Low-energy focused ultrasounds (LO-FUs, with normal intensities of 0.1-2 W/cm 2 and frequencies of 0.5-3 MHz) generate rapid oscillating pressures that lead to non-invasive hyperthermia.…”
Section: Ultrasoundsmentioning
confidence: 99%
“…Low-energy focused ultrasounds (LO-FUs, with normal intensities of 0.1-2 W/cm 2 and frequencies of 0.5-3 MHz) generate rapid oscillating pressures that lead to non-invasive hyperthermia. In response, mechanical and thermal stresses are manifested transiently without killing the cells and several genes are upregulated such as heat-shock proteins that translocate from cytoplasm to cell surface (125). Based on this response, the use of heat-shock protein's (HSP) promoters have been used for local control gene expression in several models (126) but not for immunotherapy.…”
Section: Ultrasoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, low intensity FUS (LOFU; peak negative pressures from $2 to 5 MPa) modulates the expression and cellular distribution of HSPs family protein (e.g., HSP 60,70,and 90). This was shown to enhance radiotherapy outcomes of breast and prostate murine cancers [148]. In contrast, ablative FUS rapidly debulks tumor to release tumor antigens.…”
Section: Focused Ultrasound (Fus)-based Np-isvmentioning
confidence: 99%